Teaching experiences and architectural directions in South Korea - Lecardane, Renzo; La Scala, Paola (AGATHÓN | International Journal of Architecture, Art and Design, 2018)
Over the last few years the concept of knowledge-based has acquired increasing acceptance, thus providing a new context in which knowledge may become a fundamental resource for innovation. To this end, the internationalization of academic activity is a fundamental tool for awareness in interaction in didactic and research methodology. This article presents a few thoughts regarding he teaching and research of the LabCity Architecture (DARCH-UNIPA group), on the theme of the transformation of the city of Busan, in South Korea, through the re-composition of disseminated parts of the city and the enhancement of the urban and natural heritage of the contemporary city.